Use of High-Dose Oxazaphosphorine Drugs for Treating Immune Disorders - JONES RICHARD J; BRODSKY ROBERT A (2007)
This disclosure relates, at least in part, to methods of eliminating adverse immune reactions in a subject in need thereof including those associated with autoimmune diseases, allergic reactions and transplant rejection, including administration of a lymphocytotoxic non-myeloablative amount of a oxazaphosphorine drug to the subject.